Ethnic minorities in Slovenia (1918–1955). Between destruction and coexistence - Komac, Miran (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to the issue of ethnic minorities in Slovenia from the establishment of the Kingdom of Serbs, Croats and Slovenes to the first decade after the Second World War. The aim of the study is to analyze the impact of changing state borders and nation-building processes on the situation of minorities and to examine the relationship between state policy and the aspirations of ethnic groups. The author employs a historical-political method based on the analysis of statistical data, political documents, and nationality processes occurring in Central Europe. He argues that the incorporation of Slovenia into Yugoslavia did not lead to the realization of the idea of a “United Slovenia,” since a substantial part of the Slovene population remained outside the state’s borders, particularly in Italy, Austria, and Hungary. At the same time, Italian, German, Hungarian, Croatian, and other minorities found themselves within Slovenian territory. Nationality policy was shaped by the conflict between the concept of the nation-state and the reality of a multiethnic society. The author emphasizes that minorities were often perceived as potential sources of political threats, leading to attempts at assimilation or restrictions on their influence. The conclusions indicate that nationality relations in Slovenia were shaped both by integrative processes and by conflicts resulting from nationalism and changing state borders.